Bioconjugation as a smart immobilization approach for α-amylase enzyme using stimuli-responsive Eudragit-L100 polymer: a robust biocatalyst for applications in pharmaceutical industry - Heidi Mohamed Abdel-Mageed; Rasha Ali Radwan; Nermeen Zakaria AbuelEzz; Hebatallah Ahmed Nasser; Aliaa Ali El Shamy; Rana M. Abdelnaby; Nesrine Abdelrehim EL Gohary (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Enzymes are powerful versatile biocatalysts, however, industrial application of enzymes is usually hampered by their susceptibility. Bio-inspired Eudragit-α-amylase conjugate (E-AC) was proposed as a biocatalyst for various pharmaceutical and industrial applications. In this study, α -Amylase (E.C. 3.2.1.1) was immobilized by covalent conjugation to Eudragit L-100 under mild conditions. The effect of polymer, carbodiimide and enzyme concentrations on optimization of (E-AC) was investigated. In addition, characterization of the free α -Amylase and E-AC with regard to pH, temperature, kinetic parameters, reusability and operational and storage conditions was carried out. Results showed a shift of the optimum pH of E-AC towards the alkaline side whereas, E-AC exhibited higher thermal stability at all tested temperatures. The kinetic parameters, Km values were 2.87 mg/ml and 3.15 mg/ml and Vmax values were 8.35 mg/ml/min and 8.98 mg/ml/min for free and E-AC, respectively. E-AC retained 85% of the initial activity after five consecutive amylolytic cycles, thus emphasizing its powerful potentials. Operational storage and thermal stability were highly improved as well for E-AC conjugate with an 11.6 stabilization factor in comparison to the free α-amylase. In this study, Eudragit L-100 polymer was successfully used as smart immobilization support to create a reversibly soluble-insoluble enzyme biocatalyst to enforce and extend biotechnological applications of α-amylase in the pharmaceutical industry.